Passado, presente e perspectivas para o futuro da proteção internacional de investimentos: entre a fragmentação e a coesão no Direito Internacional - Filipe Greco De Marco Leite (2017)
This paper seeks to analyse the theme of international investment protection, in the context of international law, since the earliest manifestations of such concern until its present format. In this endeavour, several categories and institutions of international law which are employed and relate to the context of international investment protection will be analysed, in order to also investigate the role of the individual and of corporations both in the context of general international law and of international investment protection. Finally, the existing interactions between international investment protection and other important agendas and interests will also be analysed, in order to demonstrate the need for consideration of interests which are external to the context of international investment protection as a precondition for the effectiveness and legitimacy of the field of international investment protection. Lastly, seeking to achieve the abovementioned effectiveness and legitimacy in the field of international investment protection, a few propositions will be drawn up in order to improve on the current framework of international investment protection.